TRANSFORMASI NILAI-NILAI KEBUDAYAAN DALAM ERA DIGITAL: ANALISIS PENGARUH MEDIA SOSIAL TERHADAP BUDAYA MASYARAKAT INDONESIA - Febriyanti Rusli, Patricia; Mega (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2023)
This study aims to analyze the influence of social media on the cultural identity of modern society. In today's rapidly developing world, human life cannot be separated from technological advances. The presence of technology has affected society and the environment over time. Currently, most people are very dependent on technology, even technology can be a basic need for everyone. Starting from parents to children who use technology in all aspects of their lives. Technology allows people to do their jobs more efficiently and quickly. The influence of rapidly developing technology also affects one of them, socio-cultural change. Socio-cultural change in Indonesia is an integral part of the dynamics of society that continues to develop. Every day we can experience how various aspects of our lives change, from our daily habits to our mindsets. Socio-cultural change is a process in which the structure, patterns, and values ​​of a society change over time. This can include changes in customs, traditions, norms, and patterns of social interaction in a society. Socio-cultural change is a complex phenomenon that is influenced by various internal and external factors. Understanding this process allows us to better understand how our society continues to adapt and develop, and how we can participate in the process of positive change.